Preparing and Studying Structural and Optical Properties of Pb1-xCdxS Nanoparticles of Solar Cells Applications (Baghdad Science Journal, 2021)
Nanoparticles of Pb1-xCdxS within the composition of 0≤x≤1 were prepared from the reaction of aqueous solution of cadmium acetate, lead acetate, thiourea, and NaOH by chemical co-precipitation. The prepared samples were characterized by UV-Vis spectroscopy(in the range 300-1100nm) to study the optical properties, AFM and SEM to check the surface morphology(Roughness average and shape) and the particle size. XRD technique was used to determine the crystalline structure, XRD technique was used to determine the purity of the phase and the crystalline structure, The crystalline size average of the nanoparticles have been found to be 20.7, 15.48, 11.9, 11.8, and 13.65 nm for PbS, Pb0.75Cd0.25S, Pb0.5Cd0.5S, Pb0.25Cd0.75S, and CdS respectively. The results indicate that crystalline structure of all prepared samples is cubic except CdS which shows hexagonal and cubic structure. The particle size was found within the range of (64.81 to 91.14) nm, with a high purity.